ESG DAN TATA KELOLA HILIRISASI CRITICAL MINERALS: MAMPUKAH INFRASTRUKTUR HUKUM INDONESIA MENJAMIN KEBERLANJUTAN DAN KEADILAN? - Baskoro, Aji (Badan Pembinaan Hukum Nasional, 2025)
AbstractThe downstreaming of critical minerals in Indonesia has become a strategic policy to support industrialization and national energy security. However, the implementation of Environmental, Social, and Governance (ESG) principles in the governance of this sector still faces regulatory and implementation challenges. Policy fragmentation, weak inter-agency coordination, and legal uncertainty pose environmental and social risks that have not been fully addressed. This study analyzes the extent to which Indonesia's legal infrastructure can ensure sustainability and justice in critical minerals downstreaming by employing a normative juridical method with a legislative and conceptual approach. The findings indicate that while ESG regulations have been incorporated into various legal instruments, their effectiveness remains constrained by weak oversight and political and economic interests. Therefore, regulatory harmonization with global ESG standards, strengthening certification mechanisms, and enhancing the role of civil society in industry oversight and accountability are necessary. Additionally, transparency in downstreaming governance must be improved to mitigate negative impacts on the environment and local communities. Further studies are required to explore the effectiveness of ESG implementation at the operational level and comparative research with other countries that have successfully integrated ESG principles into their critical minerals industry.Keywords: downstreaming, critical minerals, Environmental, Social, and Governance (ESG), legal infrastructure, sustainable governance.